Peran Faktor Teknologi, Organisasi, dan Lingkungan terhadap Transformasi Digital UMKM: Tinjauan Sistematis Literatur - Nandita Angraini; Sarah Fitriyani (Studia Ekonomika, 2026)
Digital transformation has become a strategic priority for Small and Medium-Sized Enterprises (SMEs) to enhance competitiveness, innovation, and sustainable performance in an increasingly dynamic business environment. This study aims to systematically review the roles of technological, organizational, and environmental factors in driving SMEs' digital transformation using the Technology–Organization–Environment (TOE) framework. A qualitative Systematic Literature Review (SLR) following the PRISMA 2020 guidelines was conducted by synthesizing recent peer-reviewed articles published in reputable international journals. The findings indicate that technological readiness, organizational capabilities, and environmental support collectively determine the success of digital transformation. Furthermore, digital transformation strengthens sustainable innovation capability, improves organizational performance, and enhances long-term competitiveness. The review also confirms that integrating the TOE framework with Dynamic Capability Theory provides a comprehensive perspective for understanding digital transformation in SMEs. These findings offer valuable theoretical and practical implications for researchers, policymakers, and SME managers in designing effective digital transformation strategies.